2000
DOI: 10.1001/jama.283.14.1829
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Sleep-Disordered Breathing, Sleep Apnea, and Hypertension in a Large Community-Based Study

Abstract: Our findings from the largest cross-sectional study to date indicate that SDB is associated with systemic hypertension in middle-aged and older individuals of different sexes and ethnic backgrounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

66
1,646
10
112

Year Published

2001
2001
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 2,890 publications
(1,871 citation statements)
references
References 48 publications
(28 reference statements)
66
1,646
10
112
Order By: Relevance
“…2e5 Systemic hypertension affects up to two-thirds of patients with OSA. 6,7 Some investigators have proposed that endothelial dysfunction is mechanistically implicated in a sustained increase in blood pressure 8,9 and is an early process in the development of atherosclerosis. 10,11 Patients with OSA have been shown to have endothelial dysfunction 12e15 and evidence for premature atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…2e5 Systemic hypertension affects up to two-thirds of patients with OSA. 6,7 Some investigators have proposed that endothelial dysfunction is mechanistically implicated in a sustained increase in blood pressure 8,9 and is an early process in the development of atherosclerosis. 10,11 Patients with OSA have been shown to have endothelial dysfunction 12e15 and evidence for premature atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…While dietinduced weight loss is associated with a fall in blood pressure, 19 the effects from sibutramine are less clear. 20,21 Given that OSA is a risk factor for hypertension 22 and difficult to control blood pressure, 11 there may be specific concerns in using sibutramine in obese patients with OSA. It is possible that sibutramine may initially increase blood pressure in subjects with OSA at least in the early stages of use before weight loss occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Immediate consequences of OSAS are sleep fragmentation, arousal, poor school/job performance, irritability, intermittent hypercapnia and hypoxemia, nocturnal hypertension and marked changes in autonomic control of the cardiovascular system. 88 The long-term consequences of OSAS include sustained daytime and nocturnal hypertension, 89,90 cor pulmonale, left ventricular hypertrophy 91 and increased cardiovascular and cerebrovascular morbidity and mortality. 92 Indeed, cross-sectional results from the Sleep Heart Health Study showed a strong association between OSAS, heart failure and stroke.…”
Section: Cardiovascular Risksmentioning
confidence: 99%